2016
DOI: 10.1177/0263774x16676272
|View full text |Cite
|
Sign up to set email alerts
|

Fewer voters, higher stakes? The applicability of rational choice for voter turnout in Quebec municipalities

Abstract: Municipal voter turnout is often considered to be a function of electorate size. According to the rational choice theory of voter behavior, a rational voter is more inclined to abstain in the presence of larger electorates, and more likely to participate in smaller ones. This article examines the impact of electorate size on voter turnout using a multivariate regression model to explain voter participation in Quebec municipalities in the 2009 and 2013 local elections ( N = 1040). Several other assumptions pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
11
0
3
Order By: Relevance
“…In a similar vein, the higher the number of elected terms served by the incumbent candidate, the lower turnout is expected to be (Trounstine, 2008). Additionally, the larger the margin of victory in previous elections, the lower the voter turnout is hypothesized to be; this is because voters would anticipate the outcome of the election (Breux et al, 2016). Furthermore, by definition, elections by acclamation, a relatively common phenomenon at the Canadian local level, undermine the competitiveness of elections.…”
Section: The Canadian Casementioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, the higher the number of elected terms served by the incumbent candidate, the lower turnout is expected to be (Trounstine, 2008). Additionally, the larger the margin of victory in previous elections, the lower the voter turnout is hypothesized to be; this is because voters would anticipate the outcome of the election (Breux et al, 2016). Furthermore, by definition, elections by acclamation, a relatively common phenomenon at the Canadian local level, undermine the competitiveness of elections.…”
Section: The Canadian Casementioning
confidence: 99%
“…Blank (1974) suggests that low density leads to higher turnout since voters are more likely to know candidates, thereby reducing the information costs of assessing them. In the case of Quebec, Breux and colleagues (2016) have shown that the smaller the municipality, the higher the electoral participation.…”
Section: Influences On Voter Turnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Si ces résultats tendent à minimiser la spécificité de l'échelle municipale souvent mise de l'avant, il est permis de penser que la présence éventuelle d'un déficit informationnel à cette échelle est susceptible de freiner davantage l'électorat le plus jeune dans leur mobilisation, dans la mesure où leur accès à l'information est dépendant du degré d'information que détiennent leurs parents, principales sources d'information citées au sein de notre échantillon. Si la disponibilité plus grande de l'information n'est certes pas un gage de participation électorale, elle peut toutefois participer à la réduction du « coût » du vote pour l'électeur (Breux, Couture et Goodman, 2017). L'ensemble de ces réflexions invite à se demander dans quelle mesure les réponses de nos répondants témoignent d'un problème plus vaste liée à la diffusion de l'information politique à l'échelle municipale québécoise en général.…”
unclassified
“…Cette idée n'est pas sans lien avec la théorie de l'électeur rationnel que nous avons déjà explorée ailleurs(Breux et al, 2017).…”
unclassified